What Are the Causes and Consequences of Delayed Surgery for Pediatric Tibial Spine Fractures? A Multicenter Study. Issue 3 (2nd March 2022) - Smith, Haley E.; Cruz, Aristides I.; Mistovich, R. Justin; Leska, Tomasina M.; Ganley, Theodore J.; Aoyama, Julien T.; Ellis, Henry B.; Kushare, Indranil; Lee, Rushyuan J.; McKay, Scott D.; Milbrandt, Todd A.; Rhodes, Jason T.; et al.
Background: The uncommon nature of tibial spine fractures (TSFs) may result in delayed diagnosis and treatment. The outcomes of delayed surgery are unknown. Purpose: To evaluate risk factors for, and outcomes of, delayed surgical treatment of pediatric TSFs. Study Design: Cohort study; Level of evidence, 3. Methods: The authors performed a retrospective cohort study of TSFs treated surgically at 10 institutions between 2000 and 2019. Patient characteristics and preoperative data were collected, as were intraoperative information and postoperative complications. Surgery ≥21 days after injury was considered delayed based on visualized trends in the data. Univariate analysis was followed by purposeful entry multivariate regression to adjust for confounders. Results: A total of 368 patients (mean age, 11.7 ± 2.9 years) were included, 21.2% of whom underwent surgery ≥21 days after injury. Patients who experienced delayed surgery had 3.8 times higher odds of being diagnosed with a TSF at ≥1 weeks after injury (95% CI, 1.1-14.3; P = .04), 2.1 times higher odds of having seen multiple clinicians before the treating surgeon (95% CI, 1.1-4.1; P = .03), 5.8 times higher odds of having magnetic resonance imaging (MRI) ≥1 weeks after injury (95% CI, 1.6-20.8; P < .007), and were 2.2 times more likely to have public insurance (95% CI, 1.3-3.9; P = .005). Meniscal injuries were encountered intraoperatively in 42.3% of patients with delayed surgery versus 21.0% of patients treated without delay ( P < .001), resulting in 2.8 times higher odds in multivariate analysis (95% CI, 1.6-5.0; P < .001). Delayed surgery was also a risk factor for procedure duration >2.5 hours (odds ratio, 3.3; 95% CI, 1.4-7.9; P = .006). Patients who experienced delayed surgery and also had an operation >2.5 hours had 3.7 times higher odds of developing arthrofibrosis (95% CI, 1.1-12.5; P = .03). Conclusion: Patients who underwent delayed surgery for TSFs were found to have a higher rate of concomitant meniscal injury, longer procedure duration, and more postoperative arthrofibrosis when the surgery length was >2.5 hours. Those who experienced delays in diagnosis or MRI, saw multiple clinicians, and had public insurance were more likely to have a delay to surgery.